2019
DOI: 10.3390/jcm8020214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Comorbidities on Health-Related Quality of Life among Respiratory Patients in Vietnam

Abstract: Comorbidities are common in respiratory disease patients and have been well-known to impact their quality of life. The objective of this study is to estimate the minimal clinically important difference (MCID) of the health-related quality of life (HRQOL) among respiratory disease patients with different comorbidities in a Vietnamese tertiary hospital. We performed a cross-sectional study from October to November 2016 at the Respiratory Center of Bach Mai Hospital, Hanoi, with a total of 508 participants. Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
5
22
0
Order By: Relevance
“…People with comorbidities had a lower HRQoL score than those people without, which was in the line with previous studies [68,70,71]. In respiratory patients, those who suffer from at least one chronic condition were significantly associated with decreased HRQoL [72].…”
Section: Discussionsupporting
confidence: 91%
“…People with comorbidities had a lower HRQoL score than those people without, which was in the line with previous studies [68,70,71]. In respiratory patients, those who suffer from at least one chronic condition were significantly associated with decreased HRQoL [72].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of FCs indicated that they completely (50.5%) or partially (46.9%) understood the patient's disease. The median (IQR) number of hours of caregiving per day was 20 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Table 1 shows the QOL of AL patients and FCs.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…Specifically, health-related QOL is defined as the status of physical, emotional and psychological wellbeing [10]. It is recommended that health-related QOL is evaluated along with clinical and laboratory indicators [11]. Evaluating health-related QOL informs an integral part of treatment effectiveness [12] and burden of disease [13].…”
mentioning
confidence: 99%
“…Patients selecting the option "no problem" was classified into the "No problem" group; otherwise, they were classified into the "Having problem" group. This tool has been widely used in Vietnam [37][38][39][40][41][42]. Moreover, we utilized the EQ-Visual Analogue Scale (EQ-VAS) to measure current self-rated health, with a score ranging from 0 "The worse health state that you can imagine" to 100 "The best health state that you can imagine".…”
Section: Health-related Quality Of Lifementioning
confidence: 99%